2002
DOI: 10.1016/s0277-3791(01)00114-7
|View full text |Cite
|
Sign up to set email alerts
|

Timing and warmth of the Last Interglacial period: new U-series evidence from Hawaii and Bermuda and a new fossil compilation for North America

Abstract: The timing and duration of the Last Interglacial period have been controversial, with some studies suggesting a relatively short duration that is orbitally forced and others suggesting a long duration that is at most only partly related to orbital forcing. New, high-precison thermal ionization mass spectrometric (TIMS) U-series ages of Last Interglacial corals from Hawaii and Bermuda test these competing hypotheses. Waimanalo Formation corals from slowly uplifting Oahu, Hawaii range in age from B134 to B113 ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
202
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(226 citation statements)
references
References 109 publications
(221 reference statements)
23
202
1
Order By: Relevance
“…Because of the closer proximity of California to Northern Hemisphere ice sheets of the Pleistocene, Muhs et al (2012) inferred that the higher relative sea levels on the California coast are due to GIA processes, and their modeling supports that interpretation. On the tectonically stable Atlantic Coast of the United States (Wehmiller et al, 2004) and Bermuda (Muhs et al, 2002b), marine deposits dated to~80 ka are found at elevations of 1 m to as much as~7.5 m above modern sea level. These higherthan-expected elevations have also been explained by GIA effects (Potter and Lambeck, 2003).…”
Section: Marine Terrace Ages and Sea-level Historymentioning
confidence: 99%
“…Because of the closer proximity of California to Northern Hemisphere ice sheets of the Pleistocene, Muhs et al (2012) inferred that the higher relative sea levels on the California coast are due to GIA processes, and their modeling supports that interpretation. On the tectonically stable Atlantic Coast of the United States (Wehmiller et al, 2004) and Bermuda (Muhs et al, 2002b), marine deposits dated to~80 ka are found at elevations of 1 m to as much as~7.5 m above modern sea level. These higherthan-expected elevations have also been explained by GIA effects (Potter and Lambeck, 2003).…”
Section: Marine Terrace Ages and Sea-level Historymentioning
confidence: 99%
“…On Bermuda, corals are found in emergent (+2-3 m) marine deposits that have acceptable ages ranging (using the criteria described above) from 118,900 ± 600 to 113,400 ± 900 yr B.P. (Muhs et al, 2002). The Key Largo Limestone of the Florida Keys contains abundant corals, but preservation is generally poor.…”
Section: Figmentioning
confidence: 99%
“…record apparent sea-level histories (for both the magnitude and timing of sea-level rise or fall) that differ from those distant from the ice sheets. Nevertheless, it is interesting to note that in the western Atlantic Ocean, deposits that date to the peak of the last interglacial period, from tectonically stable Bermuda (∼32 • N), the Florida Keys (∼25 • N), the Bahamas (∼24-21 • N), the Yucatan Peninsula (∼20 • N), and southern Brazil (∼30 • S) all have paleo-sea-level indicators with similar elevations, i.e., about 3-8 m above modern sea level (Szabo et al, 1978;Martin et al, 1988;Chen et al, 1991;Fruijtier et al, 2000;Muhs et al, 2002).…”
mentioning
confidence: 99%
“…For example, in the Western Atlantic Ocean, studies of constructional reef terraces from islands considered tectonically stable (e.g., Bermuda, Bahamas, Western Australia), particularly of terraces generated during the last interglacial (Marine Isotope Stage MIS 5), provided relatively precise information about the relative elevation and duration of high sea stand episodes (Chen et aL, 1991;Neumann and Hearty, 1996;Stirling et aL, 1998;Hearty, 2002;Muhs et aL, 2002;Mylroie, 2007). In a similar fashion, .…”
Section: Introductionmentioning
confidence: 99%